2020
DOI: 10.1101/2020.09.04.283713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery and prioritization of variants and genes for kidney function in >1.2 million individuals

Abstract: Chronic kidney disease (CKD) has a complex genetic underpinning. Genome-wide association studies (GWAS) of CKD-defining glomerular filtration rate (GFR) have identified hundreds of loci, but prioritization of variants and genes is challenging. To expand and refine GWAS discovery, we meta-analyzed GWAS data for creatinine-based estimated GFR (eGFRcrea) from the Chronic Kidney Disease Genetics Consortium (CKDGen, n=765,348, trans-ethnic) and UK Biobank (UKB, n=436,581, Europeans). The results (i) extend the numb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…Fine-mapping methods assign to each variant a posterior probability of being a causal variant (posterior inclusion probability, PIP) [9][10][11][12][13][14][15][16] , and recentlydeveloped methods for fine-mapping use scalable, sophisticated algorithms [14][15][16] that allow for multiple causal variants in a locus and can be applied to the very large data sets necessary to overcome the challenges listed above. Previous studies, performed almost exclusively in cohorts of European ancestry [17][18][19][20][21][22] or meta-analyses of majority European ancestry [23][24][25][26][27][28][29][30] , have used finemapping methods to identify putative causal variants, enabling novel biological insights into diseases such as inflammatory bowel disease 19 and type 2 diabetes 20 and traits such as blood cell counts 21 and kidney function 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Fine-mapping methods assign to each variant a posterior probability of being a causal variant (posterior inclusion probability, PIP) [9][10][11][12][13][14][15][16] , and recentlydeveloped methods for fine-mapping use scalable, sophisticated algorithms [14][15][16] that allow for multiple causal variants in a locus and can be applied to the very large data sets necessary to overcome the challenges listed above. Previous studies, performed almost exclusively in cohorts of European ancestry [17][18][19][20][21][22] or meta-analyses of majority European ancestry [23][24][25][26][27][28][29][30] , have used finemapping methods to identify putative causal variants, enabling novel biological insights into diseases such as inflammatory bowel disease 19 and type 2 diabetes 20 and traits such as blood cell counts 21 and kidney function 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Rather, CKD susceptibility is influenced by DNA sequence variants in many genes, environmental factors, and their interactions. Genome-wide association studies (GWAS) have successfully identified common variants at >400 genetic loci that are associated with kidney function 10,12,13 . The index variants at known eGFR-associated loci explain an estimated 8.9% of eGFR variance 12 .…”
mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have successfully identified common variants at >400 genetic loci that are associated with kidney function 10,12,13 . The index variants at known eGFR-associated loci explain an estimated 8.9% of eGFR variance 12 .…”
mentioning
confidence: 99%
“…Using the Stanzick et al eGFR meta-analysis results, there was again no observed Mendelian randomization association between the ACLY expression genetic instrument and either eGFR phenotype (eGFRcrea P = 0.83 and eGFRcys P = 0.73, Table S3). 22 Using the Gorski et al meta-analysis of rapid kidney function decline results, there was a nominal Mendelian randomization association of the ACLY expression genetic instrument with the dichotomous “Rapid3” greater than 3 ml/min/1.73m 2 per year phenotype (OR=0.88; 95% CI 0.78 to 1.00; P = 0.05, Table S3) with the weighted median model, while the inverse variance weighted model was just above the significance threshold (OR=0.88; 95% CI 0.76 to 1.01; P = 0.07, Table S3). There was no association seen with the dichotomous “CKDi25” >25% drop across the 60 ml/min/1.73m 2 threshold ( P > 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the effect of the ACLY expression instrument on eGFR in the summary-level results of the Stanzick et al eGFR meta-analysis which includes the data from CKDGen and UK biobank (n = 1,201,930) 22 , and on the “rapid3” (greater than 3 ml/min/1.73m 2 per year encompassing 34,874 cases and 107,090 controls) and “CKDi25” (25% or more decline in eGFRcrea or eGFRcys and crossing below 60 ml/min/1.73m 2 encompassing 19, 901 cases and 175,244 controls) phenotypes as defined in the meta-analysis of Gorski et al 23 Note that these analyses include overlapping CKDGen samples and cannot be viewed as independent replications.…”
Section: Methodsmentioning
confidence: 99%